KEMAMPUAN KONEKSI MATEMATIKA SISWA SMP DALAM PENYELESAIAN SOAL MATEMATIKA - Bastian, Kevin (Department of Mathematics Education , University of Jember, 2015)
Abstract. Mathematics is a study that is useful for human life such as becoming a basic of modern technology development, having an important role in many sciences and increasing human thoughts. Mathematic connection is inspired because it is not partitioned in many separated topics, but it is a unity. Besides, mathematics also can not separate from the other sciences and problems in human life. Without mathematic connection, the tudents must study and memorize too many concepts and mathemathics' procedure that is separated away from the others. Keywords: Mathematics Connection,Mathematics Problem Solving,Connection